Sustainable Facades : Design Methods for High-performance Building Envelopes. - Aksamija, Ajla (Wiley, 2013)
Buildings are the largest consumers of energy, and their facades present a significant opportunity for energy conservation. Written by an associate and head of the research lab at Perkins + Will, this book presents practical information on how to design sustainable facades that are high-performing and energy efficient. Topics covered include climate-specific design considerations; types of facades; facade materials; control of heat, air, and moisture; and emerging technologies such as smart materials, double-skin facades, facades as energy generators, and control systems. This full-color book.